Research Brief #9: Nutrition Degrees In Nepal: A Review of Current Offerings and Gaps. - Sapkota, Diplav.; Kennedy, Eileen T., 1947- (Tufts University. Tisch Library., 2016)
This briefing lays out the various Nutrition Degree programs available at higher education institutions in Nepal, and identifies gaps in formal nutrition education. Keywords: CRSP, Research Brief, Degree Programs.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy